P090 Difference between palindromic rheumatism and rheumatoid arthritis at the level of gene expression. (21st February 2018) - Ajaib, S; Droop, A; Mankia, K; Emery, P; Ponchel, F
Abstract : Introduction: Palindromic rheumatism (PR) is characterised by recurrent, episodic attacks of articular inflammation, which resolve completely without residual joint damage. Whether PR should be considered as a prodrome of rheumatoid arthritis (RA) or as a distinct syndrome remains unclear, over 70 years since first described. 1 Objectives: This project investigates whether the pathogenesis of PR and RA is similar by comparing gene expression profiles from PBMCs in PR, healthy control (HC), and early RA patients. Methods: PBMCs were obtained from drug naïve PR patients during palindromic attack (flare, n=10) and between attacks (non-flare, n=12). 12 age/sex matched, drug nave RA patients were selected from the RA-MAP project along with 12 HC. The Illumina Human-HT-12/v4 Expression BeadChip microarray and a standard data analysis workflow, were used to establish a list of differentially expressed genes (DEGs). The STRING database was used to characterise functional associations of the top DEGs between groups. 2 Only the highest confidence (0.900) interactions were selected based on prior information from text-mining, experiments and databases. Results: Comparing RA and HC, STRING analysis revealed 112 interactions (from 378 DEGs); including expected associations with genes such as TNF, AP1 (JUN/FOS), chemokines/receptors and a node including several Interferon responsive genes. Between PR non-flare and HC, 185 interactions (from 458 DEGs) were observed, featuring numerous endoplasmic reticulum and ribosomal proteins, in addition to high IL-1beta/high IL-1R1, lower IL-10 and higher SOCS3. Interestingly, lower Ubiquitin C (UBC) was found to be a prominent feature of many of the identified interactions. Comparing inflammation between RA and PR flare, 176 interactions (from 476 DEGs) included an enhanced endoplasmic/ribosomal signature, lower ubiquitination but higher sumolation and other stress-associated proteins. SCOC3, was no longer present at the top of the DEGs list when both conditions were inflammatory. The IFN signature identified in RA was still highlighted in the associations. Finally, comparing PR non-flare and flare (10 matched pairs), 125 interactions (from 434 DEGs) were observed, primarily from pathways related again to stress, ubiquitination and DNA/RNA processing. Conclusions: Although preliminary, our findings suggest there are distinct gene expression programmes used in PR and RA, and that PR pathogenesis may involve several stress response mechanisms, which are not clearly associated with top DEGs in RA pathogenesis. References: . Hench P, Rosenberg EF. Palindromic rheumatism. A 'new' oft recurring disease of joints (arthritis, periarthritis, para-arthritis) apparently producing no articular residues. Report of thirty-four cases; its relation to angio-neural arthrosis', 'allergic rheumatism' and rheumatoid arthritis. Arch Int Med 1944;73:293–321. . Szklarczyk D, Franceschini A, Wyder S, Forslund K, Heller D, Huerta-Cepas J, Simonovic M, Roth A, Santos A, Tsafou KP, Kuhn M, Bork P, Jensen LJ, von Mering C. STRING v10: Protein-protein interaction networks, integrated over the tree of life. Nucleic Acids Res2015January;43:D447–52. Disclosure of interest: None declared